Application of the Problem Based Learning Learning Model to Increase Student Motivation and Learning Outcomes in PAI Material at SMAN CMBBS Pandeglang - Loachiyah; Wasehudin; Shobri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is first, to determine the increase in student motivation with the use of problem-based learning models. Second, to determine the increase in student learning outcomes with the use of problem-based learning models. Third, to determine the effectiveness of using problem-based learning models in increasing student motivation and learning outcomes. In this study, the research method used is a quantitative research method with an experimental approach. The quantitative method is a scientific/scientific method because it meets scientific principles, namely concrete/empirical, objective, measurable, rational, and systematic. The results showed that to find out the increase in student learning motivation, the researcher collected data by distributing questionnaires to students at the beginning of learning before being given treatment using a problem-based learning model, this questionnaire aims to determine students' initial motivation, then after being given treatment using a problem-based learning model problem, for the second time the researcher distributed the same questionnaire to find out the students' final motivation. From the results of the initial and final questionnaires, an increase of 33.5% was obtained. The effectiveness of using problem-based learning models is obtained from the results of observations made during learning activities, from the results of these observations it is known that many students are involved or active in learning